Steam-Based Distance Learning on Early Childhood Education Centers in Central Java - Dina Amalia; Joko Sutarto; Yuli Kurniawati Sugiyo Pranoto (International Conference on Science, Education, and Technology, 2021)
This study aimed to define distance learning that integrates STEAM in Early Childhood Education centers in Central Java. It is a quantitative descriptive study using a survey methodology. In this study, the population and sample were teachers (n=140) at Early Childhood Education centers in Central Java. According to data processing and analysis, distance learning incorporating STEAM has primarily been implemented in Early Childhood Education centers in Central Java. Distance learning that STEAM educates children to develop higher-order thinking skills. According to the descriptive analysis calculations results, the percentage of distance learning containing STEAM received the highest score of 89 with a percentage of 64%. As a result, it is possible to conclude that distance learning incorporating STEAM has a high level of effectiveness and the belief that children will be better able to solve problems to be more effective. Many parents in this study do not understand early childhood development and the learning process during distance learning. As a result, the purpose of this article would be to explain the significance of strengthening STEAM-loaded distance learning in children to provide children with a practical learning experience by increasing cooperation between teachers and parents.